2011
DOI: 10.1111/j.1540-4781.2011.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring Interactional Competence in a Study Abroad Context: Japanese Language Learners’ Use of the Interactional Particle ne

Abstract: This study examines the development of interactional competence (Hall, 1993(Hall, , 1995 by English-speaking learners of Japanese as a foreign language (JFL) in a study abroad setting, as indexed by their use of the interactionally significant particle "ne." The analysis is based on a comparison of (a) 6 sets of conversations between JFL learners and native Japanese peers during the first week of the study abroad program, and (b) 6 sets of conversations between the same pairs of speakers during the fifth week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 55 publications
(82 reference statements)
1
47
1
Order By: Relevance
“…While the pace of learning varied between learners, Ohta concluded that the developmental sequence in alignment expressions for Japanese as a Foreign Language students appeared to be similar. Masuda's (2011) research on native English speakers learning Japanese as a second language in the study abroad setting found variation in pace of acquisition as well as a similar sequence of alignment expression development, from acknowledgment to agreement. In a related study, Ishida (2009) examined the development of IC as evidenced by changes in the use of the Japanese particle ne in the speech of a language learner studying abroad in Japan.…”
Section: Alignment Activitymentioning
confidence: 96%
“…While the pace of learning varied between learners, Ohta concluded that the developmental sequence in alignment expressions for Japanese as a Foreign Language students appeared to be similar. Masuda's (2011) research on native English speakers learning Japanese as a second language in the study abroad setting found variation in pace of acquisition as well as a similar sequence of alignment expression development, from acknowledgment to agreement. In a related study, Ishida (2009) examined the development of IC as evidenced by changes in the use of the Japanese particle ne in the speech of a language learner studying abroad in Japan.…”
Section: Alignment Activitymentioning
confidence: 96%
“…While the pace of learning varied between learners, Ohta concluded that the developmental sequence in alignment expressions for Japanese as a Foreign Language students appeared to be similar. Masuda's () research on native English speakers learning Japanese as a second language in the study abroad setting found variation in pace of acquisition as well as a similar sequence of alignment expression development, from acknowledgment to agreement. In a related study, Ishida () examined the development of IC as evidenced by changes in the use of the Japanese particle ne in the speech of a language learner studying abroad in Japan.…”
Section: Alignment Activitymentioning
confidence: 98%
“…Keywords: study abroad; fluency; Mandarin; Russian; Spanish STUDY ABROAD IS WIDELY BELIEVED TO BE a beneficial environment for language learners to develop their abilities, particularly in the domain of speaking. Most research on language development during study abroad has focused on gains in speaking skills (Llanes & Muñoz, 2009), such as oral proficiency (Hernández, 2010;Lindseth, 2010;Vande Berg, Connor-Linton, & Paige, 2009; The Modern Language Journal, 100, 3, (2016) DOI: 10.1111/modl.12343 0026-7902/16/610-624 $1.50/0 C 2016 The Modern Language Journal Watson, Siska, & Wolfel, 2013), aspects of communicative competence (Masuda, 2011;Regan, Howard, & Lemée, 2009;Shively, 2011), and phonological abilities (Díaz-Campos 2004;Knouse, 2012;Lord, 2010). These studies have greatly contributed to our understanding of the linguistic benefits of study abroad.…”
mentioning
confidence: 99%